Immunohistochemical analysis of YB-1 expression in the developing mouse eye - Nass, Alexander Florian; Wolf, Hella; Sel, Saadettin; Kalinski, Thomas; Naß, Norbert (European journal of histochemistry, 2025)
Cold shock domain (CSD) proteins, such as YB-1, play a crucial role in the regulation of transcription, mRNA stability, and translation. Consequently, YB-1 is implicated in processes such as cell differentiation, oncogenesis and oxidative stress response. The development of the eye is a complex process that involves the differentiation of numerous highly specialized cell types. We hypothesized that YB-1 is involved in both eye development and stress defense mechanisms. As an initial step, we investigated the expression of YB-1 during the embryology of the mouse eye. YB-1 mRNA could be detected by RT-PCR and sequencing the PCR product in retinal tissue of adult mice. To elucidate the expression pattern of YB-1 protein during mouse eye development, we analyzed its expression in the developing mouse eye at embryonic day 13 (E13), E15, E18 and postnatal day 14 (P14) using immunohistochemistry. Expression of the YB-1 protein was detected in all retinal cells, as well as in the corneal and lens epithelial cells, throughout all stages of eye development examined. These findings suggest that YB-1 could have a significant role in the eye, potentially related to development and differentiation.